2000
DOI: 10.1128/aac.44.9.2349-2355.2000
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Plasma Membrane H+-ATPase, an Antifungal Target inCryptococcus neoformans

Abstract: The Cryptococcus neoformans PMA1 gene, encoding a plasma membrane H ؉ -ATPase, was isolated from a genomic DNA library of serotype A strain ATCC 6352. An open reading frame of 3,380 nucleotides contains six introns and encodes a predicted protein consisting of 998 amino acids with a molecular mass of approximately 108 kDa. Plasma membranes were isolated, and the H ؉ -ATPase was shown by sodium dodecyl sulfatepolyacrylamide gel electrophoresis to be slightly larger than the S. cerevisiae H ؉ -ATPase, consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 29 publications
3
62
0
Order By: Relevance
“…The A. fumigatus enzyme in plasma membranes was found to have an optimal pH of 6.5 and displayed K m and V max values of 0.5 mM and 0.2 mol of P i released per mg of protein per min, respectively, which are typical values for fungal H ϩ -ATPases (21,26). An IC 50 of 1.8 M was found for the mechanism-specific inhibitor vanadate (5), which compares favorably with VO 4 IC 50 s of 0.8, 1.6, and 9 M for H ϩ -ATPases from S. cerevisiae (15), C. neoformans (40), and C. albicans (23), respectively.…”
Section: Discussionsupporting
confidence: 48%
“…The A. fumigatus enzyme in plasma membranes was found to have an optimal pH of 6.5 and displayed K m and V max values of 0.5 mM and 0.2 mol of P i released per mg of protein per min, respectively, which are typical values for fungal H ϩ -ATPases (21,26). An IC 50 of 1.8 M was found for the mechanism-specific inhibitor vanadate (5), which compares favorably with VO 4 IC 50 s of 0.8, 1.6, and 9 M for H ϩ -ATPases from S. cerevisiae (15), C. neoformans (40), and C. albicans (23), respectively.…”
Section: Discussionsupporting
confidence: 48%
“…A possible explanation for the ⌬isc1 strain's sensitivity to acidic stress could be the altered function of the proton pump Pma1, which is critical for maintaining the intracellular pH of C. neoformans within the physiological ranges necessary for optimal enzymatic activities and crucial metabolic processes (22). Indeed, Pma1's physiological importance is reflected by the inviability of Pma1 deletion mutants of S. cerevisiae or C. neoformans (1,41). Several reports have shed light on the role that sphingolipids have on the correct oligomerization and localization of Pma1 during its synthesis and transport to the plasma membrane (reviewed in reference 14).…”
Section: Vol 74 2006mentioning
confidence: 99%
“…Pma1 is important for the regulation of intracellular pH (22,41,42) and for the response to oxidative (40) and nitrosative (50) …”
mentioning
confidence: 99%
“…Phylogenetic analysis revealed that Apt1 from C. neoformans is closely related to P-type ATPase of the Drs2 family of APTs (P4 type) but clearly distinct from the other main classes of P-type ATPases identified so far in C. neoformans. These include the P2 types, such as the sarcoplasmic/ER Ca 2ϩ ATPase EcaI (14), the sodium/ potassium P-type ATPase Ena1 (30), the H ϩ ATPases Pma1 and Pma2 (21,53), the Ca 2ϩ /Mg 2ϩ -transporting ATPase Pmr1, and a P1-type copper-exporting ATPase, Atu2/Ccc2 (57) (see Fig. S1 in the supplemental material).…”
Section: Apt1 In C Neoformans Is Functionally Related To Drs2 In Smentioning
confidence: 99%